Analysis of Adaptation Levels to the ISO 9001:2015 Quality Management System Amendment Regarding Climate Change at PT Indocement Tunggal Prakarsa: A Case Study of Cement Production Process at Plant 14 - Zahra Fitriyana; Merita Bernik (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
Climate change poses a significant challenge to the manufacturing sector, including the cement industry, as it may affect operational performance and product quality consistency. In response, ISO 9001:2015 has been amended to emphasize organizational context and a risk-based approach, including climate-related risks. This study aims to analyze the implementation of the ISO 9001:2015 amendment related to climate change and its influence on the quality management system and cement production operations at PT Indocement Tunggal Prakarsa Plant 14, as well as to propose recommendations to accelerate the integration of climate change aspects into the quality management system. This research adopts a qualitative case study approach. Data were collected through interviews, questionnaires, observations, and document analysis, and analyzed using data reduction, data display, and conclusion drawing, supported by correlation analysis using NVivo software. The findings show that the amendment has been implemented 57% fully and 42% partially, mainly at the technical and operational levels, particularly in operational control, quality planning, and infrastructure support. However, integration at the strategic level, especially through management review, remains limited. Strengthening leadership involvement and performance evaluation is therefore essential to enhance the adaptability and sustainability of the quality management system in addressing climate change.